2019
DOI: 10.1074/mcp.ra118.000808
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-222 Attenuates Mitochondrial Dysfunction During Transmissible Gastroenteritis Virus Infection

Abstract: In BriefZhao et al. identify microRNA-222 as a mediator of mitochondrial dysfunction, THBS1, and CD47 induced during TGEV infection and showed that mi-croRNA-222 inhibits TGEV-induced mitochondrial dysfunction via targeting and downregulating CD47. Graphical Abstract Highlights• microRNA-222 attenuates TGEV-induced mitochondrial dysfunction.• microRNA-222 downregulates THBS1 and CD47.• THBS1 is the target of microRNA-222 during TGEV infection.• THBS1 and CD47 increase mitochondrial Ca 2ϩ level and reduced mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The results of the bioinformatic analysis and luciferase assay demonstrate that miR‐222 directly binds to the 3′UTR of THBS1 . In a recent study, quantitative proteomic analysis of miR‐222‐mimic‐transfected and TGEV‐infected PK‐15 cells revealed that THBS1 is a target for miR‐222 (Zhao et al, ). This result is consistent with those of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the bioinformatic analysis and luciferase assay demonstrate that miR‐222 directly binds to the 3′UTR of THBS1 . In a recent study, quantitative proteomic analysis of miR‐222‐mimic‐transfected and TGEV‐infected PK‐15 cells revealed that THBS1 is a target for miR‐222 (Zhao et al, ). This result is consistent with those of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have identified a number of miRNAs that regulate the THBS1 gene in different types of cells, e.g., miR‐487b, the miR‐17‐92 cluster, miR‐194, miR‐18 and miR‐19, miR‐27b, and miR‐let‐7d (Asama et al, ; Dogar, Semplicio, Guennewig, & Hall, ; Farberov & Meidan, ; Feng et al, ; Miao et al, ; Sundaram et al, ; van Almen et al, ). In a recent study, a quantitative proteomic analysis of PK‐15 cells that were transfected with miR‐222 mimics and infected with transmissible gastroenteritis virus (TGEV) indicated that THBS1 was regulated by miR‐222 (Zhao et al, ). However, there are few reports of miR‐222 in pGCs.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of ATF3 results in accumulation of depolarized mitochondria, and increased mitochondrial ROS production ( 37 ). In addition, Zhao et.al ( 38 ) reported that overexpression of THBS1 stimulated mitochondrial Ca 2+ levels and decreased mitochondrial membrane potential (MMP) levels, leading to mitochondrial dysfunction. These data strongly suggests that MOTS-c improves mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study implicates elevated let-7f-5p expression as a biomarker for multiple malignant diseases, including non-muscle-invasive bladder ( Shee et al., 2020 ) and prostate cancers ( Ge et al., 2020 ). miR-222a, a miR-221/222 cluster component ( Chun-Zhi et al., 2010 ), is aberrantly expressed in hepatocellular carcinoma ( Wang et al., 2019 ), epithelial tumors ( Gaetani et al., 2020 ), and virus-infected cells ( Zhao et al., 2019 ; Song et al., 2020 ). Therefore, we speculate that they may be prospective candidates for antibacterial treatments or use as prophylactic targets.…”
Section: Discussionmentioning
confidence: 99%